AKIBAT HUKUM PENGANGKATAN ANAK TANPA PENETAPAN PENGADILAN - Rini Safarianingsih (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2022)
An adopted child is stipulated in Article 1 point 1 of Government Regulation No. 54/2007 concerning the Implementation of Child Adoption. A child’s rights are shifted from parents, a legal guardian, or other who has responsible for the care, education, and the grow of child in the family environment of his or her adoptive parents. Child adoption does not only belong to married couples but also for a single women or men are allowed as long as they have a strong motivation to take care for a child. The process that must be carried out through a parent’s statement when handing over the child. Child adoption has become a familiar in Indonesia and has been housed through the Religious Courts Institution for Muslims and the State Courts Institution fornon-Muslims.Child adoption does not sever the blood relations toward his or her biological parents. In article 6 paragraph (1) states that adoptive parents are obliged to inform their adopted child of their backgrounds and biological parents, and as Article 6 paragraph (2) the notice of biological parents is carried out by considering with the readiness of the child concerned. Thus, the child adoptionis valid if a court decision has been made and recorded in the civil registry deed.